Mapping trends and hotspot regarding testicular torsion: A bibliometric analysis of global research (2000–2022) - Hu, Shaowen; Guo, Mingjie; Xiao, Yafei; Li, Yang; Luo, Qingyang; Li, Zun; Zhu, Chaoyang (Frontiers in Pediatrics, 2023)
【background】 Testicular torsion is an acute scrotal disorder requiring immediate emergency treatment. Ischemic injury and reperfusion injury are important causes of oxidative stress and irreversible oxidative damage after testicular torsion. Although a large number of literatures have discussed the causes and treatment of testicular torsion, there is currently a lack of systematic exploration of the historical evolution of testicular torsion and the construction of a knowledge framework. 【method】 The Web of Science Core Collection was searched for studies on testicular torsion published between 2000 and 2022. The basic data of the literature were analyzed by using Excel and CiteSpace software. 【result】 A total of 1007 publications on testicular torsion published were found in 64 countries between 2000 and 2022, with an increasing annual publication level. Early detection, early diagnosis and early treatment of testicular torsion had always been at the core of clinical practice, and the pathological cascade reaction of ischemic injury and ischemia-reperfusion injury after testicular torsion were also at the core of basic research. Emphasis had been placed on the development of protective drugs for ischemia and reperfusion after testicular torsion in various countries, regions and institutions. 【conclusion】 Over the past 20 years, the research on testicular torsion had been widely concerned. Hot topics in testicular torsion in recent years were ischemia-reperfusion injury, oxidative stress, rat, doppler ultrasonography, diagnosis and orchiectomy, and we predicted that the research hotspots in the next few years will still be the early diagnosis and treatment of testicular torsion and the drug research of ischemia-reperfusion injury. This article may provide a useful resource for clinicians and basic researchers regarding testicular torsion.